The Development of a self-efficacy scale for mathematical modeling competencies - ilhan koyuncu; Cem Oktay Güzeller; Didem Akyüz (International Journal of Assessment Tools in Education)
Mathematical modeling has come into prominence during the last a few decades in many countries’ mathematics teaching curricula. It combines real life situations with mathematical context. Although evaluating students’ mathematical modeling performances with a unique Likert type instrument is questionable, having an instrument about their self-efficacy beliefs in mathematical modeling may help to comment about their ideas related to their competencies in mathematical modeling. The purpose of this study is to develop a reliable and valid measurement scale to determine mathematical modeling self-efficacy of mathematics teacher candidates. For this purpose, the draft and final form of the scale was applied to a total of 562 pre-service elementary mathematics teachers from different public universities in Turkey. The findings of study revealed that the scale is unidimensional according to the results of exploratory factor analysis. The unidimensionality of the scale was validated by confirmatory factor analysis. The reliability of mathematical modeling self-efficacy scale was very high (.97). Finally, it was found that this scale is an appropriate measurement tool to evaluate students’ self-efficacy beliefs on their mathematical modeling competencies. Some suggestions related to the scale and for further studies were given at the end.